Associations Between Long‐Term Fine Particulate Matter Exposure and Mortality in Heart Failure Patients. Issue 6 (17th March 2020) - Ward‐Caviness, Cavin K.; Weaver, Anne M.; Buranosky, Matthew; Pfaff, Emily R.; Neas, Lucas M.; Devlin, Robert B.; Schwartz, Joel; Di, Qian; Cascio, Wayne E.; Diaz‐Sanchez, David
Abstract : Background: Environmental health risks for individuals with heart failure (HF) have been inadequately studied, as these individuals are not well represented in traditional cohort studies. To address this we studied associations between long‐term air pollution exposure and mortality in HF patients. Methods and Results: The study population was a hospital‐based cohort of individuals diagnosed with HF between July 1, 2004 and December 31, 2016 compiled using electronic health records. Individuals were followed from 1 year after initial diagnosis until death or the end of the observation period (December 31, 2016). We used Cox proportional hazards models to evaluate the association of annual average fine particulate matter (PM2.5 ) exposure at the time of initial HF diagnosis with all‐cause mortality, adjusted for age, race, sex, distance to the nearest air pollution monitor, and socioeconomic status indicators. Among 23 302 HF patients, a 1 μg/m 3 increase in annual average PM2.5 was associated with an elevated risk of all‐cause mortality (hazard ratio 1.13; 95% CI,  1.10–1.15). As compared with people with exposures below the current national PM2.5 exposure standard (12 μg/m 3 ), those with elevated exposures experienced 0.84 (95% CI,  0.73–0.95) years of life lost over a 5‐year period, an observation that persisted even for those residing in areas with PM2.5 concentrations below current standards. Conclusions: Residential exposure to elevated concentrations of PM2.5 is a significant mortality risk factor for HF patients. Elevated PM2.5 exposures result in substantial years of life lost even at concentrations below current national standards.